DETERMINATION OF VITAMIN CONTENT IN GREEN PEA SEEDS (Scientific journal of the Fergana State University, 2025)
This article provides information about the green pea (Pisum sativum) plant, its chemical composition, and its medicinal significance. During the study, the content of water-soluble vitamins in green pea seeds was determined using the high-performance liquid chromatography (HPLC) method. Additionally, the physicochemical properties and spectral characteristics of green peas were analyzed based on the obtained data.